Impact of haemoglobinopathies on asymptomatic Plasmodium falciparum infection and naturally acquired immunity among children in Northern Ghana - Lamptey, Helena; Seidu, Zakaria; Lopez-Perez, Mary; Kyei-Baafour, Eric; Hviid, Lars; Adjei, George Obeng; Ofori, Michael Fokuo (Frontiers in Hematology, 2023)
Background: The protective effect of certain haemoglobinopathies, such as HbS, HbC, and α-thalassaemia, against severe malaria has long been established; however, there is only limited and equivocal evidence regarding their impact on asymptomatic parasitaemia. Here, we investigated the effect of HbS, HbC, and α-thalassaemia on asymptomatic P. falciparum parasitaemia and acquired immunity among children in Northern Ghana. Materials and Methods: A cross-sectional study was conducted among 1,017 healthy children (1-17 years) in 13 malaria-endemic communities in Northern Ghana. The children were screened for structural Hb phenotypes using SickleSCAN and for P. falciparum infection using anti-HRP2 malaria RDT, subsequently confirmed by capillary electrophoresis and PCR, respectively. α-thalassaemia genotyping was done using PCR. Levels of IgG specific for six recombinant malaria antigens (PfCSP, GLURP, MSP3, Pfs230, HB3VAR06, and IT4VAR60) and crude asexual blood-stage antigens were evaluated by ELISA. Results: 266 out of the 1,017 participants had either HbAC (18%) or HbAS (8.4%), whereas 35% had α thalassaemia. Twenty-five percent and 6% HbAC individuals were co-inherited with heterozygous and homozygous α-thalassaemia respectively. Similarly, 25% and 10.5% of HbAS co-inherited heterozygous and homozygous α-thalassaemia. Asymptomatic parasitaemia rates were 23%, 24%, and 19% in those with HbAA, HbAC and HbAS, respectively. The overall parasite carriage rates in heterozygous (21%) and homozygous α-thalassaemia (25%) individuals were similar to that of individuals without α-thalassaemia (23%). P. falciparum parasite carriage risk was about three times higher among homozygous α-thalassaemia individuals with HbAC (OR = 2.97; 95% CI 0.83-10.62) and heterozygous carriers with HbAS variants (OR = 2.86; 95% CI 0.85-9.60) compared to the wildtype. In HbAS individuals, IgG levels to IT4VAR60 and HB3VAR06 were significantly lower, whereas anti-CSP levels were higher than in HbAA and HbAC. Conclusions: Co-inheritance of HbAS and HbAC with α-thalassaemia increased the risk of asymptomatic parasitaemia, an indication of a negative epistatic effect between these Hb variants. Antibody levels against non-PfEMP1 antigens were slightly higher among HbAS children, but quite similar in all study groups, indicating differences in parasite exposure.